2008
DOI: 10.1080/15476910802131519
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy for Unresectable Metastatic Melanoma: Impact of Biochemotherapy on Long-Term Survival

Abstract: The impact of systemic therapy on survival of patients with metastatic melanoma is uncertain. This retrospective analysis aimed to compare the response rates and survival of patients without prior therapy with cisplatin, vinblastine, dacarbazine and interleukin (IL)-2 who were treated with biochemotherapy (containing these drugs plus interferon-α) with those of patients who received combination chemotherapy with and without interferon-α (chemotherapy ± IFN). Records for 616 chemo-naïve patients with unresectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…The progress that has been made in the understanding of melanoma pathogenesis in the past decade has resulted in the development of novel targeted therapies such as vemurafenib and dabrafenib [3][4][5]. Both drugs inhibit the activity of mutated BRAF proteins, which are observed in 40-60% of cutaneous melanoma [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The progress that has been made in the understanding of melanoma pathogenesis in the past decade has resulted in the development of novel targeted therapies such as vemurafenib and dabrafenib [3][4][5]. Both drugs inhibit the activity of mutated BRAF proteins, which are observed in 40-60% of cutaneous melanoma [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In their retrospective analysis, Bedikian et al . [19] reported that chemotherapy-naíve patients who received biochemotherapy had a median survival duration of 12.2 months. In another retrospective analysis, Keilholz et al .…”
Section: Discussionmentioning
confidence: 99%
“…Die Monotherapie mit Zytokinen (Interferon-α, Interleukin-2) erbrachte in vergleichenden Studien zwar keine Verlängerung des medianen Überle-bens, zeigte aber zumindest für Interleukin-2 eine vermehrte Rate an Langzeitüberlebern [2]. In den USA ist Interleukin-2 daher für die Therapie des metastasierten Melanoms zugelassen worden, in Europa besteht keine Zulassung.…”
Section: Chemotherapieunclassified